The Plant Interspecific Association in the Revegetated Alpine Grasslands Determines the Productivity Stability of Plant Community Across Restoration Time on Qinghai–Tibetan Plateau - Wu, Shengnan; Wen, Lu; Dong, Shikui; Gao, Xiaoxia; Xu, Yudan; Li, Shuai; Dong, Quanming; Wessell, Kelly (Frontiers in Plant Science, 2022)
Grassland cultivation is the key measure for restoring “Black Beach”, the extremely degraded alpine meadow in the Three Rivers Source region of the Qinghai-Tibet Plateau (QTP). In this study, we examined the inter-specific relationship in the vegetation community of cultivated grasslands with different restoration time through the network analysis method. The results showed that with the extension of restoration time, the development of cultivated grasslands will lead to increasing neutral interactions among the plant species. The proportion of positive and negative associations between species in the community decreased, while the number of species-independent pairs increased significantly. The complexity of plant interspecific association (species network density) had more influence on community stability with the extension of recovery time, which can be used to quantify characteristics of community structure.